Understanding Poverty and Inequality in Egypt - World Bank (World Bank, Washington, DC, 2019)
In 2015, a large share of Egypt's population was either poor (27.8 percent) or not poor but vulnerable to falling into poverty (an additional 28.7percent); most of the poor and vulnerable lived in the governorates of Upper Egypt. Clearly the country faces a challenge, but it also has the knowledge to craft solutions. Egypt's recent reforms have started to address some of the country’s economic sustainability challenges. Targeted social protection programs must continue to be an essential element of poverty reduction policy. Looking ahead, this report calls attention to the fact that re-orienting education investments towards more effective learning that raises people's employability and productivity and putting in place policies that encourage job creation will be key to sustained poverty reduction. Revitalizing education and job creation will be important for maximizing the poverty-reducing potential of the economic reform program. One of the hallmarks of healthy economies is a substantial middle class, a group often thought to be an engine of economic growth. In Egypt, a notable share of the population, close to 30 percent, can be considered middle class. Compared to the poor and vulnerable, the middle class has higher education, more assets, and better connectivity to basic services and spends a relatively large share of income on education and health. It is clearly a goal in developing countries to enlarge the middle class in order to strengthen the overall economy.